A framework of social networks control in higher educational contexts - Jakovljevic, Maria (Array, 2021)
Educationists are urged to investigate the effect of social networks control. There is a lack of multidisciplinary studies with a focus on coercive social network control in the higher education sector. This exploratory and descriptive study presents a theoretical contemplation of social network control based on ten key elements that influence teaching and learning in higher educational environments. The paper provides a critical analysis of the impact of an economic model on social networks control and examines social engineering through the tenets of digital presence, psychological strategies and tactics. Insights into user-generated content and the learning process of manipulative assimilation that influence current ways of thinking in higher educational contexts are offered through the lens of social networks control mechanisms. A framework for social network control was derived, signifying the flow and dynamics between key elements which might impact on various aspects of social network security and its applications in Higher Education.